2021
DOI: 10.3390/cancers13010136
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid and Its Nanoparticles Are Potentiators of Oncolytic Measles Virotherapy against Breast Cancer Cells

Abstract: Oncolytic viruses (OVs) and phytochemical ursolic acid (UA) are two efficacious therapeutic candidates in development against breast cancer, the deadliest women’s cancer worldwide. However, as single agents, OVs and UA have limited clinical efficacies. As a common strategy of enhancing monotherapeutic anticancer efficacy, we explored the combinatorial chemovirotherapeutic approach of combining oncolytic measles virus (MV), which targets the breast tumor marker Nectin-4, and the anticancer UA against breast ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…36 The OMV nanoparticles were tested against BT-474 and MDA-MB-468 breast cancer cells and proved a very potential therapeutic candidate in cancer treatment. 37 It was previously published that the charged nanoparticles showed a higher clearance rate from systemic circulation as compared to neutral particles and the high positive zeta potential promotes the scavenging of the nanoparticles by anionic acidic cancer cells. Oncolytic virus nanoparticles, including foot-and-mouth disease virus (FMD), were fabricated using chitosan (CS) into a 281.2 nm size and with a 13 mV positive electrical charge to assess the anti-fungal potential for mucosal vaccines.…”
mentioning
confidence: 99%
“…36 The OMV nanoparticles were tested against BT-474 and MDA-MB-468 breast cancer cells and proved a very potential therapeutic candidate in cancer treatment. 37 It was previously published that the charged nanoparticles showed a higher clearance rate from systemic circulation as compared to neutral particles and the high positive zeta potential promotes the scavenging of the nanoparticles by anionic acidic cancer cells. Oncolytic virus nanoparticles, including foot-and-mouth disease virus (FMD), were fabricated using chitosan (CS) into a 281.2 nm size and with a 13 mV positive electrical charge to assess the anti-fungal potential for mucosal vaccines.…”
mentioning
confidence: 99%
“…Previous studies also reported that the average content of ursolic acid in the fresh Oldenlandia diffusa was as high as 7.293 ± 2.776 mg/g ( 30 ). More importantly, ursolic acid has been reported to exhibit a wide antitumor spectrum and could inhibit multiple solid tumors including breast cancer ( 31 , 32 ), colorectal cancer ( 33 , 34 ), cervical cancer ( 35 ), pancreatic cancer ( 36 ) and prostate cancer ( 37 ). Several clinical trials have also suggested that ursolic acid supplementation was well-tolerated with manageable toxicity, and could potentially improve patient remission rates in subjects with advanced solid tumors ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that ursolic acid may be an ideal glycolytic inhibitor with low toxicity and economical characteristic. Noteworthy, it has been reported that ursolic acid is highly hydrophobic which leads to its disappointing systemic bioavailability and relatively short half-life in the circulation ( 31 , 46 ). To improve its clinical applicability, ursolic acid-loaded formulations such as liposomes, nanoliposomes, nanocrystals, solid dispersions and nanoparticles are strongly encouraged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological properties of UA will be greatly altered depending upon the type and composition of the carrier nanoparticle including particle size, potential charges and biomimetic properties. In case of breast cancer UA nanoparticle delivery and its anti-cancer properties have been observed with positive results [ 150 ], however each type of cancer has its unique biological properties and various pathways are modulated. In vitro studies of various types of UA nanoparticle drug delivery systems are required to check their therapeutic potential, mechanisms of action, bioavailability, and cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%